ANALISIS PRODUKTIVITAS DAN DAMPAK LINGKUNGAN AKIBAT STRATEGI PERUBAHAN JENIS BAHAN PELEDAK DI PT SEMEN BATURAJA (PERSERO) TBK - Heddy Ardies; Tien Yustini; Omar Hendro (Program Magister Manajemen Indo Global Mandiri University, 2021)
On limestone blasting activities besides safety there are two other important factors that must be highly considered, that are productivity and environmental impacts that caused, along with the replacement of the blasting contractor at PT Semen Baturaja (Persero) Tbk and accompanied by the strategy of explosive type change that used from ANFO with electric detonator to DABEX with non electric detonator. So, it is necessary an analysis of productivity and environmental impacts that caused, whether for the better or vice versa. The research method that used is qualitative triangulation research using data from direct observation in field, managing documentation data and conducting deep interview with parties who are directly or indirectly involved on limestone blasting activities. Interview was conducted with 10 samples representing representatives of Mining Division work unit with representatives from Echelon 1, Echelon III, Echelon IV and daily workers. From the testing data obtained that the strategy of explosive type change from productivity side is better and more efficient whereas from environmental impacts caused side is not better especially with the use of DABEX which cause an increased level of vibration. Based on these results, it is necessary to make improvements to the blasting method or to find for other alternative explosives that can increase productivity but have minimal environmental impact.